English English: English - Sijabat, Maria Marsitta Gabe; Wijayanti, Indah Oktari (Goodwood Akuntansi dan Auditing Reviu, 2026)
Purpose: This inquiry aims to empirically analyze the influence of audit committee effectiveness, environmental performance, and corporate disclosure levels on the intensity of carbon emission reporting. The study focuses on corporate entities within the basic materials sector officially quoted on the Indonesia Stock Exchange throughout the 2020–2024 observation window. Research Methodology: This study employs a quantitative causal-associative design, analyzing 80 observations from 16 basic materials companies selected via purposive sampling on the IDX. Secondary data were aggregated from annual and sustainability reports, corporate websites, Program Penilaian Peringkat Kinerja Perusahaan dalam Pengelolaan Lingkungan (PROPER) ratings, and IDX databases. Hypotheses were tested using multiple linear regression and diagnostic assessments via IBM SPSS Statistics. Results: The results of the F-test indicate that audit committee effectiveness, environmental performance, and corporate disclosure simultaneously exert a significant influence on carbon emission transparency. However, the t-test results reveal a divergent pattern: while audit committee effectiveness and corporate disclosure demonstrate a positive and statistically significant impact, environmental performance remains statistically insignificant. Conclusions: Transparency in carbon emissions is more strongly affected by the quality of internal governance and media exposure than by environmental performance achievements. Limitations: Limited access to some historical documents for the period 2020–2024. Contributions: Beyond advancing the scholarly literature on green accounting, these findings offer actionable insights for regulatory bodies and management to improve the quality of carbon-related disclosures.